The Role of Digital HRM Transformation in Reducing Employee Turnover Intention: A Literature Review - Misbachul Munir; Fitri Ariani Duwi Lestari (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2026)
This study examines the role of digital transformation in Human Resource Management (HRM) in influencing employees’ turnover intention amid accelerating organizational digitalization. The study aims to analyze the relationship between digital HR transformation and turnover intention and to develop a conceptual framework explaining this relationship through psychological variables. This research uses a qualitative approach with a literature study method, analyzing relevant scholarly articles through descriptive and analytical synthesis. The findings indicate that digital HR transformation does not directly reduce turnover intention but influences it indirectly through job satisfaction, employee engagement, and organizational commitment. The effectiveness of digitalization depends on implementation quality and organizational cultural readiness. This study integrates strategic capability and organizational behavior perspectives and provides guidance for organizations to implement human-centered digital HR transformation to support sustainable employee retention.